Solvent-assisted aminolysis method of waste polyurethane material and method for preparing supramolecular adhesive by recycling waste polyurethane material
The method of preparing supramolecular adhesive by solvent-assisted amine solution and a method of mixing with polyphenol compounds to solve the problems of high amine solution temperature and cumbersome reuse operation in the prior art, and the reduction of degradation temperature and simplification of reuse operation are achieved.
Patent Information
- Application Number
- CN202311359300.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
The existing amine lysis method degrades waste polyurethane materials with high degradation temperature due to mass transfer hindered, and the reuse method based on chemical reactions is cumbersome, which increases energy consumption and cost.
By using the solvent-assisted amine solution, an amine solution is formed by mixing the catalyst with the amine solution reagent and combining it with an aprotic solvent, and added to the waste polyurethane material for degradation. At the same time, supramolecular adhesive is prepared by mixing it with polyphenol compounds to simplify the reuse of the degradation product.
The amine decomposition temperature of waste polyurethane materials is reduced, the degradation speed is accelerated, energy consumption is reduced, and the reuse process of degradation products is simplified, reducing costs.
Smart Images

Figure BDA0004502865780000061 
Figure HDA0004502865790000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycling waste polymer materials, and relates to a solvent-assisted aminolysis method of waste polyurethane materials, and a method for preparing a supramolecular adhesive by recycling degradation products of waste polyurethane materials. Background Art
[0002] Polyurethane, the full name of which is polyurethane, is the sixth largest synthetic material in the world. Polyurethane is generally a polymer with carbamate functional groups obtained by the reaction of isocyanate and polyol. Its microphase structure contains two regions: soft segment and hard segment. The soft segment is composed of polyether (ester) polyol segments, and the hard segment is composed of segments containing carbamate bonds and urea bonds with strong intermolecular hydrogen bonds. Among them, polyether polyurethane materials are polymerized by long-chain polyether polyols and polyisocyanates, and are mainly used in the fields of soft foams, elastomers, fibers, coatings and adhesives. However, a large amount of waste polyurethane materials are difficult to degrade quickly in nature, and there are problems of environmental pollution and waste of resources.
[0003] Solvent decomposition chemical recovery methods for waste polyurethane materials usually use water, alcohols or amine reagents as nucleophilic attack reagents to degrade polyurethane materials into oligomers or monomers for the synthesis of new polyurethane materials or other materials, thereby maximizing resource utilization. It is a method that is currently the focus of attention. Among them, the aminolysis method can degrade polyurethane more completely due to the high activity of the reaction reagents, and because the amino groups are introduced into the degradation products, the degradation products can be given more functions, so it has gradually attracted the attention of the industry and academia. However, during the aminolysis process, due to the interfacial wetting problem between amines and polyurethane materials, a higher temperature is required to promote the degradation reaction. In addition, there is a strong intermolecular hydrogen bond in the hard segment of the polyurethane material, which can easily lead to a higher viscosity of the reaction system, so that the mass transfer process during the reaction is hindered, which also requires the use of a higher temperature to reduce the viscosity of the reaction system. The above two factors will lead to high energy consumption in the aminolysis process of polyurethane materials.
[0004] At present, there are relatively few reports on the use of aminolysis to degrade waste polyurethane materials. CN116217914A discloses that alkylamine, small molecule alcohol and alkali metal catalyst are prepared into an aminolysis agent, and the aminolysis agent and the small pieces of waste polyurethane foam after mechanical crushing are put into a reactor, and the aminolysis is carried out after nitrogen replacement. The aminolysis temperature is 120-150°C, the reactor pressure is -0.1-0.09MPa, and the aminolysis time is 3-6h. The degradation product is mixed with sucrose or sorbitol initiator, and then reacted with epoxy monomer to obtain polyether polyol for spraying. JP6979695B2 discloses the use of polyamine to degrade polyurethane foam at a temperature higher than 180°C, and then reacted with acid anhydride to obtain amide acid, and further imidized to obtain hot melt adhesive. Grdadolnik et al. used triethylenetetramine and the like to react at 220°C for about 1h to degrade polyurethane foam. After degradation, polyether polyols were obtained by extraction for the preparation of regenerated polyurethane foam (see ACS Sustainable Chemistry & Engineering 2023, 11, 10864-10873). In the above reports on polyurethane amination, the amination reaction temperature of polyurethane materials is relatively high, and the recycling of polyurethane material degradation products is also based on chemical reactions. In order to avoid side reactions or affect the performance of regenerated products, it is often necessary to separate and purify the degradation products of polyurethane materials before obtaining the chemical reaction of the regenerated products. However, the separation and purification process is cumbersome and will increase the cost of recycling the degradation products of polyurethane materials. Therefore, it is urgent to develop a mild degradation method for waste polyurethane materials and a simpler method for recycling the degradation products of waste polyurethane materials to effectively reduce the energy consumption of the recycling process of waste polyurethane materials and reduce the cost of recycling the degradation products of polyurethane materials. Summary of the invention
[0005] Aiming at the problem that when the prior art uses the aminolysis method to degrade waste polyurethane materials, the degradation temperature is high due to the obstruction of mass transfer between amine and polyurethane materials, and the problem that the prior art method of recycling the degradation products of waste polyurethane materials based on chemical reactions causes complicated operations due to the separation and purification process of the degradation products, the present invention provides a solvent-assisted aminolysis method for waste polyurethane materials to reduce the aminolysis temperature of the waste polyurethane materials. The present invention also provides a method for recovering the degradation products of waste polyurethane materials to prepare a supramolecular adhesive, so as to simplify the recycling operation of the waste polyurethane degradation products.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0007] A solvent-assisted aminolysis method for waste polyurethane materials comprises the following steps:
[0008] The catalyst and the aminolysis reagent are fully mixed to form an aminolysis solution, the aminolysis solution is mixed with a non-protonic solvent, waste polyurethane materials are added to the obtained mixed solution, an aminolysis reaction is carried out under a heating bar to degrade the waste polyurethane materials, the non-protonic solvent and the aminolysis reagent are separated from the obtained degradation solution, and the obtained solid product is washed with water to obtain a degradation product of the waste polyurethane materials. The method can reduce the degradation temperature of the waste polyurethane materials degraded by the existing aminolysis method and accelerate the degradation speed of the waste polyurethane materials degraded by the existing aminolysis method.
[0009] In the technical scheme of the solvent-assisted aminolysis method of waste polyurethane materials mentioned above, the preferred aprotic solvents include at least one of cyclopentyl methyl ether, 1,4-dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,2-dimethoxypropane, dichloroethane, toluene, chlorobenzene, xylene, and cyclohexanone, but the feasible aprotic solvents are not limited to the preferred aprotic solvents listed above.
[0010] In the technical scheme of the solvent-assisted aminolysis method of waste polyurethane materials, the mass ratio of waste polyurethane materials to aprotic solvent is preferably controlled to be 1:(0.1-20), and further preferably, the mass ratio of waste polyurethane materials to aprotic solvent is controlled to be 1:(0.50-10).
[0011] In the technical scheme of the solvent-assisted amination method of waste polyurethane materials, the mass ratio of the waste polyurethane materials to the amination reagent is preferably controlled to be 1:(0.05-20), and further preferably, the mass ratio of the waste polyurethane materials to the amination reagent is controlled to be 1:(0.10-10).
[0012] In the technical solution of the solvent-assisted aminolysis method of waste polyurethane materials, the mass ratio of the waste polyurethane materials to the catalyst is preferably controlled to be 1:(0.01-0.30).
[0013] In the technical scheme of the solvent-assisted aminolysis method for waste polyurethane materials, the aminolysis agent is at least one of n-propylamine, isopropylamine, n-butylamine, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, ethanolamine and diethanolamine.
[0014] In the technical solution of the solvent-assisted aminolysis method of the above waste polyurethane materials, the catalyst is a catalyst used in the existing aminolysis method to degrade waste polyurethane materials, including at least one of alkali metal hydroxides, alkali metal alkoxides, acetates and organic bases. For example, the alkali metal hydroxide can be sodium hydroxide, potassium hydroxide, cesium hydroxide, etc., the alkali metal alkoxide can be potassium ethoxide, sodium ethoxide, tert-butyl potassium, etc., the acetate can be potassium acetate, zinc acetate, etc., and the organic base can be 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, tetramethylguanidine, etc., but the feasible catalyst is not limited to the specific alkali metal hydroxides, alkali metal alkoxides, acetates and organic bases listed above.
[0015] In the technical solution of the solvent-assisted aminolysis method of waste polyurethane materials, the temperature of the aminolysis reaction is preferably controlled to be 40-150°C, and more preferably, the temperature of the aminolysis reaction is controlled to be 50-100°C.
[0016] In the technical scheme of the solvent-assisted amination method of waste polyurethane materials mentioned above, different amination temperatures will affect the degradation rate of waste polyurethane materials. Generally speaking, the degradation rate of waste polyurethane materials increases with the increase of amination temperature. For example, in order to achieve the same degradation rate, the amination reaction time required for a higher amination temperature will be relatively shorter, and the amination reaction time required for a lower amination temperature will be relatively longer. Considering factors such as comprehensive energy consumption and degradation efficiency, it is preferred to control the amination reaction time to be 1 to 10 hours.
[0017] In the technical scheme of the solvent-assisted aminolysis method of waste polyurethane materials, the aminolysis reaction can be carried out under normal pressure or pressurized conditions, that is, the aminolysis reaction can be carried out in a normal pressure reaction device or a pressurized reaction device.
[0018] For achieving the degradation of waste polyurethane materials, the above-mentioned technical solution of the solvent-assisted aminolysis method of waste polyurethane materials is applicable to various types of polyurethane materials. For preparing supramolecular adhesives by the method of the present invention after achieving the degradation of waste polyurethane materials, the preferred waste polyurethane material is polyether polyurethane. Furthermore, the forms of the waste polyurethane materials include foam plastics, elastomers, spandex, adhesives, coatings, etc., but are not limited to these material forms.
[0019] In the technical scheme of the solvent-assisted aminolysis method of the above-mentioned waste polyurethane material, the affinity of the aprotic solvent and the polyether segment of the waste polyurethane material is good, and the ability of the aprotic solvent to penetrate into the waste polyurethane material polymer chain (especially the polyether segment) is stronger. When the aprotic solvent penetrates into the waste polyurethane material polymer chain, part of the aminolysis reagent can be brought in, which can promote the contact of the aminolysis reagent with the polymer chain of the waste polyurethane material, improve the interfacial wetting performance of the aminolysis reagent to the partial segment of the waste polyurethane material (especially the polyether segment), thereby promoting the contact of the aminolysis reagent with the carbamate bond of the waste polyurethane material. At the same time, because the catalyst enhances the alkalinity of the aminolysis reagent, and then enhances the intermolecular hydrogen bonding between the aminolysis reagent and the carbamate bond or urea bond in the hard segment of the waste polyurethane material, the crystallization in the hard segment of the waste polyurethane material is more easily destroyed. Further, under the reaction conditions, the aminolysis reagent can break the carbamate bond or urea bond in the hard segment of the waste polyurethane material, which promotes the dispersion of the molecular chain of the waste polyurethane material in the reaction system. Therefore, under the joint action of the aprotic solvent, the aminolysis agent and the catalyst, the mass transfer in the degradation reaction of the waste polyurethane material is promoted, thereby reducing the degradation temperature of the waste polyurethane material, thereby reducing the degradation energy consumption of the waste polyurethane material.
[0020] The technical solution of the solvent-assisted aminolysis method of the above-mentioned waste polyurethane material can reduce the degradation temperature of the waste polyurethane material degraded by the existing aminolysis method, and accelerate the degradation rate of the waste polyurethane material degraded by the existing aminolysis method. In particular, relative to the aminolysis method of waste polyurethane materials without adding aprotic solvents used in the prior art, the technical solution provided by the present invention can effectively reduce the degradation temperature of waste polyurethane materials and accelerate the degradation rate. For example, under the same degradation temperature conditions, the technical solution of the present invention can achieve a degradation rate equivalent to or higher than the aminolysis method without adding aprotic solvents used in the prior art in a shorter time. For another example, under the same degradation time conditions, the technical solution of the present invention can achieve a degradation rate equivalent to or higher than the aminolysis method without adding aprotic solvents used in the prior art at a lower degradation temperature. In addition, the technical solution of the present invention can reduce the temperature of the aminolysis of waste polyurethane materials to below 100°C, which is impossible for the prior art to use the aminolysis method to degrade waste polyurethane materials.
[0021] In the technical scheme of the solvent-assisted aminolysis method of the above-mentioned waste polyurethane material, the method of separating the aprotic solvent and the aminolysis agent from the obtained degradation liquid can be reduced pressure distillation, atmospheric pressure distillation, room temperature evaporation, etc. The recovered aprotic solvent and aminolysis agent can be reused to reduce the degradation cost of the waste polyurethane.
[0022] In the technical solution of the solvent-assisted aminolysis method of the above-mentioned waste polyurethane material, in order to increase the contact degree between the waste polyurethane material and the aminolysis reagent, the aprotic solvent and the catalyst and improve the degradation efficiency, it is preferred to crush the waste polyurethane material into a smaller size before aminolysis. The smaller the size after crushing, the more conducive to aminolysis, but the crushing cost will increase as the size of the material after crushing decreases. In actual application, the scale range of the waste polyurethane material can be determined according to the actual application requirements. Usually, the waste polyurethane material can be crushed into granules, for example, it can be crushed into granules not exceeding 5 mm.
[0023] The present invention also provides a method for preparing a supramolecular adhesive by recycling degradation products of waste polyurethane materials. The method comprises fully and uniformly mixing the degradation products of the waste polyurethane materials obtained by solvent-assisted aminolysis of the waste polyurethane materials with polyphenol compounds at 60 to 120° C. to obtain the supramolecular adhesive, and controlling the mass ratio of the degradation products of the waste polyurethane materials to the polyphenol compounds to be 1:(0.5 to 5).
[0024] Furthermore, in the technical solution of the method for recycling degradation products of waste polyurethane materials to prepare supramolecular adhesives, the polyphenol compounds include at least one of tannic acid, catechins and epigallocatechin gallate.
[0025] In the technical scheme of the method for preparing supramolecular adhesive by recycling degradation products of waste polyurethane materials, the mixture is fully stirred and mixed at 60-120° C. until the components are evenly dispersed. The stirring time may vary depending on the stirring method, stirring conditions and preparation scale.
[0026] Since the degradation products obtained by degrading waste polyurethane materials (especially polyether polyurethane materials) by aminolysis are mixtures of polyether polyols and urea compounds, if they are used separately, further separation and purification are required. The present invention directly mixes the waste polyurethane degradation products with polyphenol compounds, uniformly disperses the polyphenol compounds in the waste polyurethane degradation products, and uses the intermolecular forces (such as hydrogen bonds) between the waste polyurethane degradation products and the polyphenol compounds to fix the polyphenol compounds in the waste polyurethane degradation products, and finally forms a supramolecular adhesive. The complicated separation and purification steps of the degradation products are avoided, and the utilization methods of the degradation products of waste polyurethane materials are expanded. Compared with the utilization method of the prior art of separating and purifying the waste polyurethane degradation products and then adding expensive and highly toxic isocyanates for polymerization, the method of directly mixing the waste polyurethane degradation products with polyphenol compounds to form a supramolecular adhesive of the present invention has the characteristics of low cost, simple operation, and safer and more environmentally friendly.
[0027] The present invention has been verified through experiments that the supramolecular adhesive prepared by the present invention has good thermal stability and is recyclable and can be reused by heating. Compared with the prior art, the technical solution provided by the present invention produces the following beneficial technical effects:
[0028] 1. The present invention provides a solvent-assisted aminolysis method for waste polyurethane materials. By improving the solvent system of the aminolysis reaction, adding aprotic solvents on the basis of the aminolysis reagents and coordinating with catalysts, the degradation temperature of the existing aminolysis method for degrading waste polyurethane materials can be effectively reduced, and the degradation speed of the existing aminolysis method for degrading waste polyurethane materials can be accelerated. Under the same degradation temperature conditions, the method of the present invention can achieve a degradation rate equivalent to or higher than the aminolysis method without adding aprotic solvents used in the prior art in a shorter time. Under the same degradation time conditions, the method of the present invention can achieve a degradation rate equivalent to or higher than the aminolysis method without adding aprotic solvents used in the prior art at a lower degradation temperature. The method of the present invention can reduce the temperature of the aminolysis of waste polyurethane materials to below 100°C, which is impossible to achieve by the aminolysis method for degrading waste polyurethane materials in the prior art. The method of the present invention can effectively reduce the energy consumption of the aminolysis reaction of waste polyurethane materials, greatly reduce the aminolysis cost, and has important application value in the field of recycling and utilization of waste polyurethane materials.
[0029] 2. The solvent-assisted amination method for waste polyurethane materials provided by the present invention includes the step of separating aprotic solvent and amination reagent from the obtained degradation liquid. Specifically, the aprotic solvent and the amination reagent can be recovered by reduced pressure distillation, atmospheric pressure distillation, room temperature evaporation, etc., thereby achieving the reuse of the aprotic solvent and the amination reagent, which is also beneficial to reducing the degradation cost of waste polyurethane.
[0030] 3. The present invention also provides a method for preparing a supramolecular adhesive by recycling waste polyurethane degradation products, wherein the waste polyurethane degradation products are directly mixed with polyphenol compounds, the polyphenol compounds are uniformly dispersed in the waste polyurethane degradation products, and the polyphenol compounds are fixed in the waste polyurethane degradation products by using the intermolecular forces (such as hydrogen bonds) between the waste polyurethane degradation products and the polyphenol compounds, and finally a supramolecular adhesive is formed, and the present invention verifies through experiments that the supramolecular adhesive has good bonding properties. Compared with the existing method of utilizing waste polyurethane degradation products through chemical reactions, the present invention can avoid the complicated separation and purification steps of degradation products, and can also avoid the operation of adding expensive and highly toxic isocyanates for polymerization. The method of utilizing waste polyurethane degradation products provided by the present invention has the advantages of simple operation, low cost, simple operation, safety and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1Figures (a) and (b) are the DSC curves and TG curves of the supramolecular adhesive prepared in Example 23. DETAILED DESCRIPTION
[0032] The following examples further illustrate the solvent-assisted aminolysis method of waste polyurethane materials provided by the present invention and the method for recovering and preparing supramolecular adhesives. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. According to the above invention content, the technical personnel in the relevant field make some non-essential improvements and adjustments to the present invention for specific implementation, which still falls within the scope of protection of the present invention.
[0033] It is worth noting that in the following embodiments and comparative examples:
[0034] (1) The degradation rate of waste polyurethane materials is calculated according to the following formula:
[0035]
[0036] In the above formula, X1 is the ratio of the peak area of urethane bond to the peak area of ether bond in the degradation product, and X2 is the ratio of the peak area of urethane bond to the peak area of ether bond in the waste polyurethane material. A1 is the peak area of carbamate bonds in the degradation products, B1 is the peak area of ether bonds in the degradation products, A2 is the peak area of carbamate bonds in the waste polyurethane materials, and B2 is the peak area of ether bonds in the waste polyurethane materials.
[0037] (2) The bonding strength of the supramolecular adhesive was tested according to the method in GB / T 7124-2008.
[0038] (3) The types of the waste polyurethane materials are all polyether polyurethane materials.
[0039] Example 1
[0040] The catalyst tetramethylguanidine and the aminolysis reagent ethylenediamine are fully mixed to form an aminolysis solution, the aminolysis solution is mixed with aprotic solvent tetrahydrofuran, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste polyurethane elastomer to the aminolysis reagent is controlled to be 1:0.1, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.025, and the waste polyurethane elastomer is heated at 50° C. for 10 hours to perform an aminolysis reaction to degrade the waste polyurethane elastomer, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the aminolysis reagent, and the obtained solid product is washed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0041] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:0.5 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0042] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 1.70 MPa.
[0043] Example 2
[0044] The catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene and the amination reagent n-propylamine are fully mixed to form an amination solution, the amination solution is mixed with a non-protonic solvent tetrahydrofuran, and waste polyurethane soft foam is added to the obtained mixed solution, the mass ratio of the waste polyurethane soft foam to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane soft foam to the amination reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane soft foam to the catalyst is controlled to be 1:0.1, heating is carried out at 50°C for 6h to perform an amination reaction to degrade the waste polyurethane soft foam, the obtained degradation solution is distilled under reduced pressure to separate the non-protonic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane soft foam.
[0045] The degradation product of the waste polyurethane soft foam was mixed with tannic acid in a mass ratio of 1:1, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0046] In this embodiment, the degradation rate of waste polyurethane soft foam is 96%, and the average bonding strength of the supramolecular adhesive to glass is 2.35 MPa.
[0047] Example 3
[0048] The catalyst KOH and zinc acetate (the mass ratio of KOH to zinc acetate is 2:1) are fully mixed with the amination reagents diethylenetriamine and diethanolamine (the mass ratio of diethylenetriamine to diethanolamine is 1:1) to form an amination solution, the amination solution is mixed with aprotic solvents tetrahydrofuran and dichloroethane (the mass ratio of tetrahydrofuran to dichloroethane is 6:4), waste polyurethane fiber (waste spandex) is added to the obtained mixed solution, the mass ratio of the waste spandex to the aprotic solvent is 1:10, the mass ratio of the waste spandex to the amination reagent is 1:10, and the mass ratio of the waste spandex to the catalyst is 1:0.3, heating at 70°C for 2h to carry out an amination reaction to degrade the waste spandex, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, the obtained solid product is rinsed with water, and dried to obtain a solid degradation product of waste spandex.
[0049] The degradation product of the waste spandex was mixed with tannic acid and catechin in a mass ratio of 1:2:3, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0050] In this embodiment, the degradation rate of waste spandex is 98%, and the average bonding strength of the supramolecular adhesive to glass is 2.51 MPa.
[0051] Example 4
[0052] The catalyst KOH and the amination reagent ethanolamine are fully mixed to form an amination solution, the amination solution is mixed with the aprotic solvent 2-methyltetrahydrofuran, and waste polyurethane soft foam is added to the obtained mixed solution, the mass ratio of the waste polyurethane soft foam to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste polyurethane soft foam to the amination reagent is controlled to be 1:0.1, and the mass ratio of the waste polyurethane soft foam to the catalyst is controlled to be 1:0.025, and the waste polyurethane soft foam is heated at 50° C. for 10 hours to perform an amination reaction to degrade the waste polyurethane soft foam, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane soft foam.
[0053] The degradation product of the obtained waste polyurethane soft foam was mixed with epigallocatechin gallate in a mass ratio of 1:0.5, and stirred at 80° C. for 30 minutes to obtain a supramolecular adhesive.
[0054] In this embodiment, the degradation rate of waste polyurethane soft foam is 100%, and the average bonding strength of the supramolecular adhesive to glass is 1.82 MPa.
[0055] Example 5
[0056] The catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene is fully mixed with the amination reagents diethylenetriamine and triethylenetetramine (the mass ratio of diethylenetriamine to triethylenetetramine is 2:3) to form an amination solution, the amination solution is mixed with the aprotic solvent 2-methyltetrahydrofuran, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.1, and the waste polyurethane elastomer is degraded by heating at 70°C for 3h to perform an amination reaction, and the obtained degradation solution is decompressed and distilled to separate the aprotic solvent and the amination reagent, and the obtained solid product is washed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0057] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:1 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0058] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 2.23 MPa.
[0059] Example 6
[0060] The catalyst KOH and tetramethylguanidine (the mass ratio of KOH to tetramethylguanidine is 1:2) are fully mixed with the amination reagents diethanolamine and triethylenetetramine (the mass ratio of diethanolamine to triethylenetetramine is 4:6) to form an amination solution, the amination solution is mixed with aprotic solvents 2-methyltetrahydrofuran and dichloromethane (the mass ratio of 2-methyltetrahydrofuran to dichloromethane is 6:4), and waste polyurethane coating is added to the obtained mixed solution, the mass ratio of the waste polyurethane coating to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane coating to the amination reagent is controlled to be 1:10, and the mass ratio of the waste polyurethane coating to the catalyst is controlled to be 1:0.3, heating at 70°C for 2h to carry out an amination reaction to degrade the waste polyurethane coating, the obtained degradation solution is decompressed and distilled to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane coating.
[0061] The degradation product of the waste spandex was mixed with tannic acid and catechin in a mass ratio of 1:2:3, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0062] In this embodiment, the degradation rate of the waste polyurethane coating is 98%, and the average bonding strength of the supramolecular adhesive to the glass is 2.41 MPa.
[0063] Example 7
[0064] The catalyst tetramethylguanidine and the amination reagent diethylenetriamine are fully mixed to form an amination solution, the amination solution is mixed with the aprotic solvent ethylene glycol dimethyl ether, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:0.1, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.025, and the waste polyurethane elastomer is heated at 70°C for 10 hours to perform an amination reaction to degrade the waste polyurethane elastomer, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0065] The degradation product of the obtained waste polyurethane elastomer was mixed with epigallocatechin gallate in a mass ratio of 1:0.5, and stirred at 80° C. for 30 min to obtain a supramolecular adhesive.
[0066] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 1.89 MPa.
[0067] Example 8
[0068] The catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene is fully mixed with the amination reagents diethanolamine and ethanolamine (the mass ratio of diethanolamine to ethanolamine is 3:2) to form an amination solution, the amination solution is mixed with the aprotic solvent ethylene glycol dimethyl ether, and waste polyurethane soft foam is added to the obtained mixed solution, the mass ratio of the waste polyurethane soft foam to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane soft foam to the amination reagent is 1:5, and the mass ratio of the waste polyurethane soft foam to the catalyst is 1:0.1, heating is carried out at 70°C for 6h to perform an amination reaction to degrade the waste polyurethane soft foam, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane soft foam.
[0069] The degradation product of the waste polyurethane soft foam was mixed with tannic acid in a mass ratio of 1:1, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0070] In this embodiment, the degradation rate of waste polyurethane soft foam is 100%, and the average bonding strength of the supramolecular adhesive to glass is 2.44 MPa.
[0071] Example 9
[0072] The catalysts zinc acetate and tetramethylguanidine (the mass ratio of zinc acetate to tetramethylguanidine is 1:2) and the amination reagents diethanolamine and diethylenetriamine (the mass ratio of diethanolamine to diethylenetriamine is 4:6) are fully mixed to form an amination solution, the amination solution is mixed with aprotic solvents ethylene glycol dimethyl ether and 2-methyltetrahydrofuran (the mass ratio of ethylene glycol dimethyl ether to 2-methyltetrahydrofuran is 6:4), waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:10, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.3, heating at 70°C for 2h to carry out an amination reaction to degrade the waste polyurethane elastomer, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, the obtained solid product is rinsed with water, and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0073] The degradation product of the waste polyurethane elastomer was mixed with tannic acid and catechin in a mass ratio of 1:2:3, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0074] In this embodiment, the degradation rate of waste polyurethane soft foam is 100%, and the average bonding strength of the supramolecular adhesive to glass is 2.12 MPa.
[0075] Example 10
[0076] The catalyst potassium acetate and the aminolysis reagent triethylenetetramine are fully mixed to form an aminolysis solution, the aminolysis solution is mixed with the aprotic solvent ethylene dichloride, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste polyurethane elastomer to the aminolysis reagent is controlled to be 1:0.1, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.025, and the waste polyurethane elastomer is heated at 100° C. for 10 hours to perform an aminolysis reaction to degrade the waste polyurethane elastomer, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the aminolysis reagent, and the obtained solid product is washed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0077] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:0.5 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0078] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 1.79 MPa.
[0079] Embodiment 11
[0080] The catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene is fully mixed with the aminolysis reagents n-butylamine and diethanolamine (the mass ratio of n-butylamine to diethanolamine is 2:3) to form an aminolysis solution, the aminolysis solution is mixed with the aprotic solvent ethylene dichloride, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane elastomer to the aminolysis reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.1, and the mixture is heated at 100°C for 6h to perform an aminolysis reaction to degrade the waste polyurethane elastomer, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the aminolysis reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0081] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:1 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0082] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 2.13 MPa.
[0083] Example 12
[0084] The catalyst NaOH and tetramethylguanidine (the mass ratio of NaOH to tetramethylguanidine is 1:2) are fully mixed with the amination reagents diethanolamine and ethanolamine (the mass ratio of diethanolamine to ethanolamine is 4:6) to form an amination solution, the amination solution is mixed with aprotic solvents ethylene dichloride and ethylene glycol dimethyl ether (the mass ratio of dichloroethane to ethylene glycol dimethyl ether is 6:4), and waste polyurethane soft foam is added to the obtained mixed solution, the mass ratio of the waste polyurethane soft foam to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane soft foam to the amination reagent is controlled to be 1:10, and the mass ratio of the waste polyurethane soft foam to the catalyst is controlled to be 1:0.3, and the waste polyurethane soft foam is heated at 80°C for 2h to perform an amination reaction to degrade the waste polyurethane soft foam, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane soft foam.
[0085] The degradation product of the waste polyurethane soft foam was mixed with tannic acid in a mass ratio of 1:1, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0086] In this embodiment, the degradation rate of waste polyurethane soft foam is 96%, and the average bonding strength of the supramolecular adhesive to glass is 2.03 MPa.
[0087] Embodiment 13
[0088] The catalyst CsOH and the amination reagent ethanolamine are fully mixed to form an amination solution, the amination solution is mixed with the aprotic solvent 1,2-dimethoxypropane, and waste polyurethane soft foam is added to the obtained mixed solution, the mass ratio of the waste polyurethane soft foam to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste polyurethane soft foam to the amination reagent is controlled to be 1:0.1, and the mass ratio of the waste polyurethane soft foam to the catalyst is controlled to be 1:0.025, heating at 100° C. for 10 hours to carry out an amination reaction to degrade the waste polyurethane soft foam, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane soft foam.
[0089] The degradation product of the obtained waste polyurethane soft foam was mixed with tannic acid in a mass ratio of 1:0.5, and stirred at 80° C. for 30 minutes to obtain a supramolecular adhesive.
[0090] In this embodiment, the degradation rate of waste polyurethane soft foam is 100%, and the average bonding strength of the supramolecular adhesive to glass is 1.98 MPa.
[0091] Embodiment 14
[0092] The catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene is fully mixed with the aminolysis reagents n-butylamine and ethanolamine (the mass ratio of n-butylamine to ethanolamine is 1:4) to form an aminolysis solution, the aminolysis solution is mixed with the aprotic solvent 1,2-dimethoxypropane, and waste polyurethane coating is added to the obtained mixed solution, the mass ratio of the waste polyurethane coating to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane coating to the aminolysis reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane coating to the catalyst is controlled to be 1:0.1, and the mixture is heated at 100°C for 6 hours to perform an aminolysis reaction to degrade the waste polyurethane coating, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the aminolysis reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane coating.
[0093] The degradation product of the waste spandex was mixed with tannic acid in a mass ratio of 1:1, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0094] In this embodiment, the degradation rate of the waste polyurethane coating is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 2.41 MPa.
[0095] Embodiment 15
[0096] The catalysts zinc acetate and tetramethylguanidine (the mass ratio of zinc acetate to tetramethylguanidine is 1:2) and the amination reagents diethanolamine and diethylenetriamine (the mass ratio of diethanolamine to diethylenetriamine is 2:8) are fully mixed to form an amination solution, the amination solution is mixed with aprotic solvents 1,2-dimethoxypropane and 1,4-dioxane (the mass ratio of 1,2-dimethoxypropane to 1,4-dioxane is 6:4), waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:10, the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.3, the mixture is heated at 100°C for 1h to carry out an amination reaction to degrade the waste polyurethane elastomer, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, the obtained solid product is rinsed with water, and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0097] The degradation product of the waste polyurethane elastomer was mixed with tannic acid and epigallocatechin gallate in a mass ratio of 1:2:3, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0098] In this embodiment, the degradation rate of the waste polyurethane elastomer is 99%, and the average bonding strength of the supramolecular adhesive to the glass is 2.52 MPa.
[0099] Example 16
[0100] The catalyst KOH and the amination reagent ethanolamine are fully mixed to form an amination solution, the amination solution is mixed with the aprotic solvent 1,4-dioxane, and waste polyurethane fiber (waste spandex) is added to the obtained mixed solution, the mass ratio of the waste spandex to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste spandex to the amination reagent is controlled to be 1:0.1, and the mass ratio of the waste spandex to the catalyst is controlled to be 1:0.025, and the waste spandex is heated at 100°C for 10 hours to perform an amination reaction to degrade the waste spandex, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of waste spandex.
[0101] The degradation products of the waste spandex were mixed with tannic acid in a mass ratio of 1:0.5, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0102] In this embodiment, the degradation rate of waste spandex is 100%, and the average bonding strength of the supramolecular adhesive to glass is 1.86 MPa.
[0103] Embodiment 17
[0104] The catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene is fully mixed with the amination reagents diethanolamine and ethanolamine (the mass ratio of diethanolamine to ethanolamine is 1:4) to form an amination solution, the amination solution is mixed with the aprotic solvent 1,4-dioxane, and waste polyurethane soft foam is added to the obtained mixed solution, the mass ratio of the waste polyurethane soft foam to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane soft foam to the amination reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane soft foam to the catalyst is controlled to be 1:0.1, and the waste polyurethane soft foam is heated at 100° C. for 6 hours to perform an amination reaction to degrade the waste polyurethane soft foam, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane soft foam.
[0105] The degradation product of the waste polyurethane soft foam was mixed with tannic acid in a mass ratio of 1:1, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0106] In this embodiment, the degradation rate of waste polyurethane soft foam is 100%, and the average bonding strength of the supramolecular adhesive to glass is 2.33 MPa.
[0107] Embodiment 18
[0108] The catalyst potassium acetate and tetramethylguanidine (the mass ratio of potassium acetate to tetramethylguanidine is 1:2) are fully mixed with the amination reagents diethanolamine and diethylenetriamine (the mass ratio of diethanolamine to diethylenetriamine is 3:7) to form an amination solution, the amination solution is mixed with the aprotic solvent 1,4-dioxane and cyclopentyl methyl ether (the mass ratio of 1,4-dioxane to cyclopentyl methyl ether is 6:4), and waste polyurethane fiber (waste spandex) is added to the obtained mixed solution, the mass ratio of the waste spandex to the aprotic solvent is 1:10, the mass ratio of the waste spandex to the amination reagent is 1:10, and the mass ratio of the waste spandex to the catalyst is 1:0.3, heating at 100°C for 1h to carry out an amination reaction to degrade the waste spandex, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of waste spandex.
[0109] The degradation product of the waste spandex was mixed with tannic acid and epigallocatechin gallate in a mass ratio of 1:2:3, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0110] In this embodiment, the degradation rate of waste spandex is 97%, and the average bonding strength of the supramolecular adhesive to glass is 2.15 MPa.
[0111] Embodiment 19
[0112] The catalyst potassium acetate and the aminolysis reagent ethylenediamine are fully mixed to form an aminolysis solution, the aminolysis solution is mixed with the aprotic solvent cyclopentyl methyl ether, and waste polyurethane fiber (waste spandex) is added to the obtained mixed solution, the mass ratio of the waste spandex to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste spandex to the aminolysis reagent is controlled to be 1:0.1, and the mass ratio of the waste spandex to the catalyst is controlled to be 1:0.025, and the waste spandex is heated at 100°C for 6 hours to perform an aminolysis reaction to degrade the waste spandex, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the aminolysis reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of waste spandex.
[0113] The degradation product of the waste spandex was mixed with tannic acid in a mass ratio of 1:0.5, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0114] In this embodiment, the degradation rate of waste spandex is 100%, and the average bonding strength of the supramolecular adhesive to glass is 2.21 MPa.
[0115] Embodiment 20
[0116] The catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene is fully mixed with the amination reagents diethanolamine and n-butylamine (the mass ratio of diethanolamine to n-butylamine is 2:3) to form an amination solution, the amination solution is mixed with the aprotic solvent cyclopentyl methyl ether, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.1, and the waste polyurethane elastomer is heated at 100° C. for 3 hours to perform an amination reaction to degrade the waste polyurethane elastomer, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is washed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0117] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:1 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0118] In this embodiment, the degradation rate of the waste polyurethane elastomer is 96%, and the average bonding strength of the supramolecular adhesive to the glass is 2.42 MPa.
[0119] Embodiment 21
[0120] The catalyst NaOH and tetramethylguanidine (the mass ratio of NaOH to tetramethylguanidine is 1:2) are fully mixed with the amination reagents diethanolamine and ethanolamine (the mass ratio of diethanolamine to ethanolamine is 2:8) to form an amination solution, the amination solution is mixed with aprotic solvents cyclopentyl methyl ether and toluene (the mass ratio of cyclopentyl methyl ether to toluene is 6:4), and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:10, the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.3, the waste polyurethane elastomer is heated at 100°C for 1h to perform an amination reaction to degrade the waste polyurethane elastomer, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0121] The degradation product of the waste polyurethane elastomer was mixed with tannic acid and epigallocatechin gallate in a mass ratio of 1:2:3, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0122] In this embodiment, the degradation rate of the waste polyurethane elastomer is 97%, and the average bonding strength of the supramolecular adhesive to the glass is 2.03 MPa.
[0123] Embodiment 22
[0124] The catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene and the amination reagent ethanolamine are fully mixed to form an amination solution, the amination solution is mixed with the aprotic solvent toluene, and waste polyurethane fiber (waste spandex) is added to the obtained mixed solution, the mass ratio of the waste spandex to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste spandex to the amination reagent is controlled to be 1:0.1, and the mass ratio of the waste spandex to the catalyst is controlled to be 1:0.025, and the waste spandex is heated at 100°C for 6 hours to perform an amination reaction to degrade the waste spandex, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of waste spandex.
[0125] The degradation products of the waste spandex were mixed with tannic acid in a mass ratio of 1:0.5, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0126] In this embodiment, the degradation rate of waste spandex is 100%, and the average bonding strength of the supramolecular adhesive to glass is 1.94 MPa.
[0127] Embodiment 23
[0128] The catalyst NaOH is fully mixed with the amination reagents ethanolamine and n-butylamine (the mass ratio of ethanolamine to n-butylamine is 3:2) to form an amination solution, the amination solution is mixed with the aprotic solvent toluene, and waste polyurethane fiber (waste spandex) is added to the obtained mixed solution, the mass ratio of the waste spandex to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste spandex to the amination reagent is controlled to be 1:5, and the mass ratio of the waste spandex to the catalyst is controlled to be 1:0.1, and the waste spandex is heated at 100°C for 3h to perform an amination reaction to degrade the waste spandex, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of waste spandex.
[0129] The degradation product of the waste spandex was mixed with tannic acid in a mass ratio of 1:1, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0130] In this embodiment, the degradation rate of waste spandex is 100%, and the average bonding strength of the supramolecular adhesive to glass is 1.99 MPa.
[0131] The thermal stability of the supramolecular adhesive prepared in this embodiment was tested, and its DSC curve and TG curve were as follows: Figure 1 As shown in Figures (a) and (b), it can be seen that there is no obvious thermal change in the supramolecular adhesive within the supramolecular adhesive preparation temperature range of 60 to 120°C, indicating that the supramolecular adhesive does not experience thermal decomposition and chemical reaction in this temperature range, and should have good reusability.
[0132] The first average bonding strength of the supramolecular adhesive to glass was 1.99 MPa. After the first bonding, the second bonding was performed after heating and scraping. The average bonding strength of the third bonding to glass was 1.88 MPa. After the second bonding, the third bonding was performed after heating and scraping. The average bonding strength of the third bonding to glass was 1.86 MPa. When repeated bonding, the bonding strength did not decrease significantly, indicating that the supramolecular adhesive provided by the present invention has reusability.
[0133] Embodiment 24
[0134] The catalysts potassium acetate and tetramethylguanidine (the mass ratio of potassium acetate to tetramethylguanidine is 1:2) are fully mixed with the amination reagents diethanolamine and tetraethylenepentamine (the mass ratio of diethanolamine to tetraethylenepentamine is 3:7) to form an amination solution, the amination solution is mixed with aprotic solvents toluene and ethylene glycol diethyl ether (the mass ratio of toluene to ethylene glycol diethyl ether is 6:4), waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:10, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.3, heating at 100°C for 1h to carry out an amination reaction to degrade the waste polyurethane elastomer, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, the obtained solid product is rinsed with water, and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0135] The degradation product of the waste polyurethane elastomer was mixed with tannic acid and catechin in a mass ratio of 1:1.2:0.8, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0136] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 2.30 MPa.
[0137] Embodiment 25
[0138] The catalyst tetramethylguanidine and the aminolysis reagent ethanolamine are fully mixed to form an aminolysis solution, the aminolysis solution is mixed with the aprotic solvent ethylene glycol dimethyl ether, and waste polyurethane elastomer is added to the obtained mixed solution, and the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste polyurethane elastomer to the aminolysis reagent is controlled to be 1:0.1, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.025. The waste polyurethane elastomer is heated at 100° C. for 6 hours to perform an aminolysis reaction to degrade the waste polyurethane elastomer, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the aminolysis reagent. The obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0139] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:0.5 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0140] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 2.11 MPa.
[0141] Embodiment 26
[0142] The catalyst KOH is fully mixed with the amination reagents diethanolamine and n-butylamine (the mass ratio of diethanolamine to n-butylamine is 2:3) to form an amination solution, the amination solution is mixed with the aprotic solvent ethylene glycol dimethyl ether, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.1, and the waste polyurethane elastomer is heated at 100° C. for 3 hours to perform an amination reaction to degrade the waste polyurethane elastomer, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is washed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0143] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:1 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0144] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 2.34 MPa.
[0145] Embodiment 27
[0146] The catalyst NaOH and tetramethylguanidine (the mass ratio of NaOH to tetramethylguanidine is 1:2) are fully mixed with the amination reagents diethanolamine and diethylenetriamine (the mass ratio of diethanolamine to diethylenetriamine is 3:7) to form an amination solution, the amination solution is mixed with the aprotic solvents ethylene glycol dimethyl ether and 1,2-dimethoxypropane (the mass ratio of ethylene glycol dimethyl ether to 1,2-dimethoxypropane is 6:4), and waste polyurethane soft foam is added to the obtained mixed solution, the mass ratio of the waste polyurethane soft foam to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane soft foam to the amination reagent is controlled to be 1:10, and the mass ratio of the waste polyurethane soft foam to the catalyst is controlled to be 1:0.3, and the waste polyurethane soft foam is heated at 100°C for 1h to perform an amination reaction to degrade the waste polyurethane soft foam, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane soft foam.
[0147] The degradation product of the waste polyurethane soft foam was mixed with tannic acid and catechin in a mass ratio of 1:2:3, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0148] In this embodiment, the degradation rate of waste polyurethane soft foam is 97%, and the average bonding strength of the supramolecular adhesive to glass is 2.55 MPa.
[0149] Embodiment 28
[0150] The catalyst NaOH and the aminolysis reagent ethanolamine are fully mixed to form an aminolysis solution, the aminolysis solution is mixed with the aprotic solvent cyclohexanone, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:0.5, the mass ratio of the waste polyurethane elastomer to the aminolysis reagent is controlled to be 1:0.1, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.025, and the waste polyurethane elastomer is heated at 150° C. for 2 h to perform an aminolysis reaction to degrade the waste polyurethane elastomer, and the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the aminolysis reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0151] The degradation product of the obtained waste polyurethane elastomer was mixed with epigallocatechin gallate in a mass ratio of 1:0.5, and stirred at 80° C. for 30 min to obtain a supramolecular adhesive.
[0152] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 1.92 MPa.
[0153] Embodiment 29
[0154] The catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene is fully mixed with the amination reagents diethanolamine and ethanolamine (the mass ratio of diethanolamine to ethanolamine is 3:2) to form an amination solution, the amination solution is mixed with the aprotic solvent cyclohexanone, and waste polyurethane elastomer is added to the obtained mixed solution, the mass ratio of the waste polyurethane elastomer to the aprotic solvent is controlled to be 1:5, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.1, and the waste polyurethane elastomer is heated at 150° C. for 3 hours to perform an amination reaction to degrade the waste polyurethane elastomer, the obtained degradation solution is distilled under reduced pressure to separate the aprotic solvent and the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0155] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:1 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0156] In this embodiment, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 2.32 MPa.
[0157] Embodiment 30
[0158] The catalysts zinc acetate and tetramethylguanidine (the mass ratio of zinc acetate to tetramethylguanidine is 1:2) and the amination reagents diethanolamine and diethylenetriamine (the mass ratio of diethanolamine to diethylenetriamine is 4:6) are fully mixed to form an amination solution, the amination solution is mixed with aprotic solvents ethylene glycol dimethyl ether and 2-methyltetrahydrofuran (the mass ratio of ethylene glycol dimethyl ether to 2-methyltetrahydrofuran is 6:4), waste polyurethane soft foam is added to the obtained mixed solution, the mass ratio of the waste polyurethane soft foam to the aprotic solvent is controlled to be 1:10, the mass ratio of the waste polyurethane soft foam to the amination reagent is controlled to be 1:10, and the mass ratio of the waste polyurethane soft foam to the catalyst is controlled to be 1:0.3, heating at 100°C for 1h to carry out an amination reaction to degrade the waste polyurethane soft foam, the obtained degradation solution is decompressed and distilled to separate the aprotic solvent and the amination reagent, the obtained solid product is rinsed with water, and dried to obtain a solid degradation product of the waste polyurethane soft foam.
[0159] The degradation product of the waste polyurethane soft foam was mixed with tannic acid and catechin in a mass ratio of 1:2:3, and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0160] In this embodiment, the degradation rate of waste polyurethane soft foam is 98%, and the average bonding strength of the supramolecular adhesive to glass is 1.98 MPa.
[0161] Comparative Example 1
[0162] The catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene is fully mixed with the amination reagents diethylenetriamine and triethylenetetramine (the mass ratio of diethylenetriamine to triethylenetetramine is 2:3) to form an amination solution, waste polyurethane elastomer is added to the amination solution, the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.1, and the waste polyurethane elastomer is degraded by heating at 70°C for 3h to perform an amination reaction, and the obtained degradation solution is distilled under reduced pressure to separate the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0163] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:1 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0164] In this example, the degradation rate of the waste polyurethane elastomer is 48%. Since the degradation rate of the waste polyurethane elastomer is too low, the supramolecular adhesive prepared in this comparative example does not have bonding properties to glass.
[0165] Both Example 5 and Comparative Example 1 were subjected to an aminolysis reaction at 70° C. for 3 h. After the addition of the aprotic solvent in Example 5, the degradation rate of the waste polyurethane elastomer increased from 48% in Comparative Example 1 to 100%, indicating that the present invention can effectively increase the degradation rate of waste polyurethane materials by adding an aprotic solvent.
[0166] Comparative Example 2
[0167] The catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene is fully mixed with the amination reagents diethylenetriamine and triethylenetetramine (the mass ratio of diethylenetriamine to triethylenetetramine is 2:3) to form an amination solution, and waste polyurethane elastomer is added to the amination solution, and the mass ratio of the waste polyurethane elastomer to the amination reagent is controlled to be 1:5, and the mass ratio of the waste polyurethane elastomer to the catalyst is controlled to be 1:0.1. The waste polyurethane elastomer is degraded by heating and reflux at 140°C for 3h to perform an amination reaction, and the obtained degradation solution is distilled under reduced pressure to separate the amination reagent, and the obtained solid product is rinsed with water and dried to obtain a solid degradation product of the waste polyurethane elastomer.
[0168] The degradation product of the waste polyurethane elastomer was mixed with tannic acid in a mass ratio of 1:1 and stirred at 80°C for 30 minutes to obtain a supramolecular adhesive.
[0169] In this comparative example, the degradation rate of the waste polyurethane elastomer is 100%, and the average bonding strength of the supramolecular adhesive to the glass is 2.12 MPa.
[0170] In Example 5 and Comparative Example 2, the aminolysis reaction was carried out for 3 hours. After adding the aprotic solvent, in Example 5, when the aminolysis time was 3 hours, only an aminolysis temperature of 70° C. was required to make the degradation rate of the waste polyurethane elastomer reach 100%, while in Comparative Example 2, when the aprotic solvent was not added, the aminolysis temperature needed to be increased to 140° C. to make the degradation rate of the waste polyurethane elastomer reach 100% when the aminolysis time was 3 hours. This shows that the present invention can effectively reduce the degradation temperature of waste polyurethane materials by adding aprotic solvents.
Claims
1. A solvent-assisted aminolysis method for waste polyurethane materials, characterized in that: The following steps are involved: The catalyst and the aminolysis reagent are fully mixed to form an aminolysis solution, the aminolysis solution is mixed with a non-protonic solvent, waste polyurethane materials are added to the obtained mixed solution, an aminolysis reaction is carried out under heating conditions to degrade the waste polyurethane materials, the non-protonic solvent and the aminolysis reagent are separated from the obtained degradation solution, and the obtained solid product is washed with water to obtain a degradation product of the waste polyurethane materials. The method can reduce the degradation temperature of the waste polyurethane materials degrading by the existing aminolysis method and accelerate the degradation speed of the waste polyurethane materials degrading by the existing aminolysis method.
2. The solvent-assisted aminolysis method of waste polyurethane materials according to claim 1, characterized in that: The aprotic solvent includes at least one of cyclopentyl methyl ether, 1,4-dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,2-dimethoxypropane, ethylene dichloride, toluene, chlorobenzene, xylene, and cyclohexanone.
3. The solvent-assisted aminolysis method of waste polyurethane materials according to claim 1, characterized in that: The mass ratio of waste polyurethane material to aprotic solvent is controlled to be 1:(0.1-20).
4. The solvent-assisted aminolysis method of waste polyurethane materials according to claim 1, characterized in that: The mass ratio of waste polyurethane material to the aminolysis agent is controlled to be 1:(0.05-20), and the mass ratio of waste polyurethane material to the catalyst is controlled to be 1:(0.01-0.30).
5. The solvent-assisted aminolysis method of waste polyurethane materials according to any one of claims 1 to 4, characterized in that: The aminolysis agent is at least one of n-propylamine, isopropylamine, n-butylamine, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, ethanolamine and diethanolamine.
6. The solvent-assisted aminolysis method of waste polyurethane materials according to any one of claims 1 to 4, characterized in that: The catalyst is at least one of alkali metal hydroxide, alkali metal alkoxide, acetate and organic base.
7. The solvent-assisted aminolysis method of waste polyurethane materials according to any one of claims 1 to 4, characterized in that: The temperature of the aminolysis reaction is controlled to be 40-150°C.
8. The solvent-assisted aminolysis method of waste polyurethane materials according to any one of claims 1 to 4, characterized in that: The waste polyurethane material is polyether polyurethane.
9. A method for preparing supramolecular adhesive by recycling degradation products of waste polyurethane materials, characterized in that: The degradation product of the waste polyurethane material obtained by the method according to any one of claims 1 to 8 is fully mixed with the polyphenol compound at 60-120° C. to obtain a supramolecular adhesive, and the mass ratio of the degradation product of the waste polyurethane material to the polyphenol compound is controlled to be 1:(0.5-5).
10. The method for preparing supramolecular adhesive by recycling degradation products of waste polyurethane materials according to claim 9, characterized in that: The polyphenol compound includes at least one of tannic acid, catechin and epigallocatechin gallate.
Citation Information
Patent Citations
Manufacturing method of hot melt adhesive using waste materials
JP6979695B2
Process for processing waste polyurethane
CN104494006A
Method for recycling waste thermosetting resin and composite material thereof
CN109897216A
Method for degrading, recycling and reusing polyurethane
CN113402770A
Method for preparing polyether polyol for spraying by aminolysis of waste polyurethane foam
CN116217914A
Cited By
Polyurethane degradation method and application
CN120795410A
Flame-retardant disassembling agent of polyurethane adhesive and lossless disassembling method of power battery pack
CN121885831A